ПРЕОБРАЗОВАНИЕ АНТРОПОГЕННОГО РЕЛЬЕФА В РАЙОНАХ РАЗРАБОТОК РОССЫПНЫХ МЕСТОРОЖДЕНИЙ (СЕВЕР ХАБАРОВСКОГО КРАЯ) - Махинов А.Н.; Махинова А.Ф. (My University, 2006)
In the regions of placer deposits of Priokhotie erosion plays the major role in the transformation of disturbed lands. The result is the mitigation of the contrast between the anthropogenic and natural landforms.
Keywords: 551.4.438.5:622.2(571.62)